INNOVATION OF TEACHERS PJOK TOWARDS THE STRATEGY OF APPLYING ONLINE LEARNING OF PHYSICAL EDUCATION IN JUNIOR HIGH SCHOOL IN THE ERA OF PANDEMIC COVID 19 - Raja Syaifullah Sihombing; Shidqi Hamdi Pratama Putera; Aghus Sifaq; Toho Cholik Mutohir; Suroto Suroto (Journal Physical Education, Health and Recreation, 2022)
This study aims to analyze and describe how a teacher's innovation in managing the strategy of applying online learning of physical education sports and health in the era of pandemic covid 19. The importance of this research in organizing the strategy of applying online learning of physical education in the era of pandemic covid 19, a pjok teacher must be able to innovate to continue to provide physical education learning by using online during the pandemic covid 19 so that innovation, and the idea of creativity pjok learning is needed by pjok teachers so that students do not experience saturation. The subject of this research is pjok teachers who number 30 people. This research is qualitative research through data collection techniques, namely interviews, observations and document searches with descriptive qualitative data analysis. Based on the results and discussion of the research, conclude the final report of this study as follows. (1) The resources of the strategy of implementing online learning of physical education that is efficient and effective and easy to understand by the dominant students come from the initiative of the teacher pjok itself. One of the reasons is the desire to implement proper physical education learning even if it is virtual. (2) The role of pjok teachers is very high can run online learning pjok well to maximize learning pjok. (3) Collaboration between pjok teachers and parents determines success in pjok online learning method program. Keywords : Pandemic covid-19, Online learning pjok